Interventional trials in atypical parkinsonism. (January 2016) - Eschlböck, S.; Krismer, F.; Wenning, G.K.
Abstract: Atypical parkinson disorders (APD) are rapidly progressive neurodegenerative diseases with a variable clinical presentation that may even mimic Parkinson's disease. Multiple system atrophy (MSA), progressive supranuclear palsy (PSP) and corticobasal degeneration (CBD) are commonly summarized under this umbrella term. Significant developments in research have expanded knowledge and have broadened available symptomatic treatments, particularly for the treatment of neurogenic orthostatic hypotension. Nonetheless, symptomatic support still remains limited in all of these disorders. Currently, there exists no effective treatment to delay disease progression and disease-modifying trials have failed to provide coherent and convincing results. Recent trials of rasagiline (in MSA), rifampicin (in MSA), tideglusib (in PSP) and davunetide (in PSP) reported negative results. Nevertheless, large cohorts of patients were recruited for interventional studies in the last few years which improved our understanding of trial methodology in APDs immensely. In addition, remarkable progress in basic research has been reported recently and will provide a solid foundation for future therapeutic trials. In this review, we will summarize published randomized, placebo-controlled clinical trials (RCTs) in APDs. Additionally, the design of ongoing and unpublished interventions will be presented. Highlights: We summarize randomized, controlled trials of MSA, PSP and CBD. We focus on symptomatic and disease-modifying trials. In the last few years trial methodology in APDs improved immensely. Symptomatic and disease-modifying treatment remains limited.